2004
DOI: 10.1021/ic0499695
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations of the Electronic Structure and Spectroscopy of Mononuclear, Non-Heme {Fe−NO}6 Complexes

Abstract: The unusual metal coordination and spin-state of the Fe(III) center in nitrile hydratase (NHase) has stimulated the synthesis of numerous model complexes in efforts to understand the reactivity and spectroscopic properties of the enzyme. A particular problem has been the development of model Fe(III) complexes that exhibit reversible, photolabile binding to nitric oxide (NO) in a manner similar to that observed for the NHase metal center. We now report a detailed NBO analysis of the ground-state chemical bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Theoretical investigations into the electronic structure of 1 reveal the existence of a LMCT transition in the visible range that corresponds to an electron promoted from a MO composed primarily of nonbonding p orbitals associated with the oxygen and nitrogen atoms of the carboxamido moiety into the Fe-NO p* antibonding MO. 10 Our results so far strongly suggest that the NO photolability of 1 is critically connected to the deprotonated carboxamido moiety. When the carboxamido nitrogen is replaced by an imine nitrogen in the analogous Schiff base ligand SBPy 3 , there is no reaction between the Fe(III) complex [(SBPy 3 )Fe(DMF)](ClO 4 ) 3 and NO.…”
Section: Introductionmentioning
confidence: 59%
“…Theoretical investigations into the electronic structure of 1 reveal the existence of a LMCT transition in the visible range that corresponds to an electron promoted from a MO composed primarily of nonbonding p orbitals associated with the oxygen and nitrogen atoms of the carboxamido moiety into the Fe-NO p* antibonding MO. 10 Our results so far strongly suggest that the NO photolability of 1 is critically connected to the deprotonated carboxamido moiety. When the carboxamido nitrogen is replaced by an imine nitrogen in the analogous Schiff base ligand SBPy 3 , there is no reaction between the Fe(III) complex [(SBPy 3 )Fe(DMF)](ClO 4 ) 3 and NO.…”
Section: Introductionmentioning
confidence: 59%
“…From this singlet excited state, relatively efficient interconversion and intersystem crossing to lower energy triplet excited states can occur. Rapid solvation of such triplet species could be competitive with other deactivation pathways and account for NO photolability 20,40. Optimization of the lowest energy triplet excited states of 1 , 2 and 3 reveal elongated Ru-NO bond lengths (1.936, 1.937, and 1.926 Å respectively) compared to those observed in the calculated singlet states (1.726, 1.732, and 1.742 Å respectively).…”
Section: Resultsmentioning
confidence: 94%
“…63 However, the electronic properties of these complexes, investigated by recent DFT calculations, have suggested that this unit can be described as a low-spin Fe 2+ coordinated to a NO + unit. 60,64 On photolysis, a low-spin Fe III center is produced which is well-characterized by EPR, Mössbauer, and resonance Raman spectroscopy. 1,6 Note that, from the XAS near-edge transitions, we know that the chemical nature of the CysS − does not change upon photolysis, and hence it serves as a spectator of the change in Z eff of the Fe ion in this process.…”
Section: Discussionmentioning
confidence: 99%